2023
DOI: 10.3390/ijms242115672
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of CYP3A4 by the KCa1.1 Inhibition Is Responsible for Overcoming Resistance to Doxorubicin in Cancer Spheroid Models

Susumu Ohya,
Junko Kajikuri,
Hiroaki Kito
et al.

Abstract: The large-conductance Ca2+-activated K+ channel, KCa1.1, plays a pivotal role in cancer progression, metastasis, and the acquisition of chemoresistance. Previous studies indicated that the pharmacological inhibition of KCa1.1 overcame resistance to doxorubicin (DOX) by down-regulating multidrug resistance-associated proteins in the three-dimensional spheroid models of human prostate cancer LNCaP, osteosarcoma MG-63, and chondrosarcoma SW-1353 cells. Investigations have recently focused on the critical roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…As shown in Figure 3 A, the expression level of CEBPD was increased by the 3D spheroid formation of LNCaP cells. In a previous study, CEBPB was also up-regulated together with 3D spheroid formation [ 2 ]. Therefore, we examined the effects of the siRNA-mediated inhibition of CEBPB and CEBPD on the expression level of FBXW7 transcripts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 3 A, the expression level of CEBPD was increased by the 3D spheroid formation of LNCaP cells. In a previous study, CEBPB was also up-regulated together with 3D spheroid formation [ 2 ]. Therefore, we examined the effects of the siRNA-mediated inhibition of CEBPB and CEBPD on the expression level of FBXW7 transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Balamurugan et al reported the involvement of the transcriptional regulator CE in the inhibition of FBXW7 expression in cancer cells [15]. As shown in Figure 3A expression level of CEBPD was increased by the 3D spheroid formation of LNCaP In a previous study, CEBPB was also up-regulated together with 3D spheroid form [2]. Therefore, we examined the effects of the siRNA-mediated inhibition of CEBPB CEBPD on the expression level of FBXW7 transcripts.…”
Section: Involvement Of Cebpd In the Kca11 Inhibition-induced Up-regu...mentioning
confidence: 84%
See 3 more Smart Citations